2017
DOI: 10.1016/j.jcis.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyhedral oligomeric silsesquioxane based cross-linked inorganic-organic nanohybrid as adsorbent for selective removal of acidic dyes from aqueous solution

Abstract: A cross-linked polyhedral oligomeric silsesquioxane (POSS) nanohybrid is synthesized through Schiff base chemistry by using octa-amino POSS as building blocks and glutaraldehyde as dual functional reagent. The obtained nanohybrid is characterized by FT-IR, solid-state Si NMR, SEM, TEM, TGA and N adsorption-desorption isotherm, and the results demonstrate the successful cross-linkage between POSS molecules, forming block-like irregular nanoparticles with a specific surface area of 42.8mg. As a novel solid-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Figure a shows that the experiments taken under optimized conditions (5 mL of 50 mg·L –1 acid blue 117 containing 100 mg·L –1 electrolytes) indicated that there is no such negative impact on the adsorption potential of silk nanofibers in the presence of electrolytes either cations or anions, suggesting its consistent behavior in the electrolyte dye effluent mixture. The addition of electrolytes can cause to decline in dye solubility by increasing electric double layers between the adsorbent and the aqueous medium . Generally, it is anticipated that addition of electrolytes can encourage hydrophobic interfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a shows that the experiments taken under optimized conditions (5 mL of 50 mg·L –1 acid blue 117 containing 100 mg·L –1 electrolytes) indicated that there is no such negative impact on the adsorption potential of silk nanofibers in the presence of electrolytes either cations or anions, suggesting its consistent behavior in the electrolyte dye effluent mixture. The addition of electrolytes can cause to decline in dye solubility by increasing electric double layers between the adsorbent and the aqueous medium . Generally, it is anticipated that addition of electrolytes can encourage hydrophobic interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of electrolytes can cause to decline in dye solubility by increasing electric double layers between the adsorbent and the aqueous medium. 37 Generally, it is anticipated that addition of electrolytes can encourage hydrophobic interfaces. Therefore, improved hydrophobic interactions in the existence of these ions can also be a source of complete dye removal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%